2014
DOI: 10.1213/ane.0000000000000246
|View full text |Cite
|
Sign up to set email alerts
|

Topical and Peripheral Ketamine as an Analgesic

Abstract: Ketamine, in subanesthetic doses, produces systemic analgesia in chronic pain settings, an action largely attributed to block of N-methyl-D-aspartate receptors in the spinal cord and inhibition of central sensitization processes. N-methyl-D-aspartate receptors also are located peripherally on sensory afferent nerve endings, and this provided the initial impetus for exploring peripheral applications of ketamine. Ketamine also produces several other pharmacological actions (block of ion channels and receptors, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(22 citation statements)
references
References 96 publications
0
22
0
Order By: Relevance
“…Therefore, ketamine may reduce the development of chronic postoperative pain via NMDA receptor blockade, which reduces wind-up and central sensitization. [11] …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, ketamine may reduce the development of chronic postoperative pain via NMDA receptor blockade, which reduces wind-up and central sensitization. [11] …”
Section: Discussionmentioning
confidence: 99%
“…[11] It also acts as a noncompetitive N -methyl- d -aspartate (NMDA) receptor antagonist, which reduces acute postoperative pain and prevents the development of chronic postoperative pain. [11] It may be administered perioperatively for postoperative pain as an adjuvant to systemic opioids, with fewer adverse effects [12] ; however, the effects of perioperative ketamine infusion on postoperative pain following BABA robotic or endoscopic thyroidectomy have not been investigated. We hypothesized that low doses of ketamine infused during surgery would reduce postoperative pain.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, various studies pointed out great anti-depressive effect of ketamine (13). Ketamine can also act as an analgesic by blocking N-methyl-D-aspartate receptors (14). New applications of ketamine emerge nowadays, such as the less established treatment for post-traumatic epilepsy, and anesthesia in the emergency department and operating theater setting (14, 15).…”
Section: Introductionmentioning
confidence: 99%
“…Other studies used ketamine topically after tonsillectomy; the treatment produced an analgesic effect and decreased the need for rescue medication. [14][15][16] Satilmiş et al 12 investigated the efficacy of adding ketamine to local anesthetic agents to increase the duration of regional anesthesia and postoperative analgesia during surgical extraction of third molars. They concluded that the combination of a local anesthetic and sub-anesthetic doses of ketamine can produce good local anesthesia.…”
Section: Discussionmentioning
confidence: 99%